SOCIO-ECONOMIC FACTORS AND DEVELOPMENT DIRECTIONS OF IMPROVING THE QUALITY OF EMPLOYMENT (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This scientific article comprehensively analyzes the theoretical and practical aspects of the concept of quality of employment. The study deeply studies the main structural elements of employment quality - income stability, working conditions, formality of employment, social protection, professional development opportunities, and work-life balance. In conditions of low quality of employment, negative consequences such as reduced labor productivity, slowed development of human capital, and increased poverty are scientifically highlighted. Based on the results of the study, practical recommendations were developed to improve employment policy and expand quality employment.
Keywords: quality of employment, decent work, labor market, stable employment, human capital, social protection.